A new strategy for co-composting dairy manure with rice straw: Addition of different inocula at three stages of composting. (June 2015) - Zhou, Cheng; Liu, Zhang; Huang, Zhao-Lin; Dong, Ming; Yu, Xiao-Long; Ning, Ping
Highlights: A new inoculation strategy of composting. Dividing inocula into three parts and respectively inoculating at three stages of composting. Inoculating proper microorganisms at appropriate time to improve composting process. Abstract: In considering the impact of inoculation time and the characteristics of composting material and inoculants on the usefulness of inoculation, a new composting strategy has been proposed and studied, in which three inocula were inoculated at three stages of composting process respectively: inoculum A ( Thermoactinomyces sp. GF1 and GF2) was inoculated before fermentation to increase or maintain high temperature of pile, inoculum B ( Coprinus cinerea and Coprinus comatus ) was inoculated after thermophilic phase to promote degradation of lignin, and inoculum C ( Trichoderma harzianum and Rhizopus oryzae ) was inoculated after 30-day fermentation to promote degradation of cellulose. The results showed that the inoculations could significantly enhance the temperature of pile and the degradation of lignocelluloses. When inocula A, B, and C were inoculated into pile, temperature increased from 25 °C to 65 °C, from 33 °C to 39 °C and from 33 °C to 38 °C respectively and 35% lignin and 43% cellulose had been degraded in inoculated pile compared to the degradation of 15% lignin and 25% cellulose in control pile. As a result, the C/N ratio dropped more rapidly degraded in the inoculated pile (reached 20 after 33-day fermentation) than that in the control pile (reached 21.7 after 45-day fermentation). In addition, the volume loss in inoculated pile (76.5%) was higher than that in control pile (53.2%). The study, therefore, indicated that inoculating proper microorganisms at appropriate time improved the composting process and our new composting strategy would be propitious to the co-composting dairy manure with rice straw.